The Influence of ESG Disclosure on Stock Prices of Banking Companies - Dewi, Desak Putu Ratna; Musmini, Lucy Sri (Dinasti Publisher, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on stock prices of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. The study is grounded in signaling theory, which suggests that non-financial information can be used by companies to convey quality and future prospects to investors. A quantitative approach was employed using panel data regression analysis, with the sample selected through purposive sampling. The independent variables consist of environmental, social, and governance disclosure, while the dependent variable is stock price. The results indicate that ESG disclosure does not have a significant effect on stock prices in the banking sector, either partially or simultaneously. These findings suggest that ESG information has not yet demonstrated strong value relevance in investment decision-making within the banking industry, as investors tend to prioritize financial information over non-financial disclosures. Furthermore, ESG disclosure in Indonesian banking remains largely compliance-driven and relatively homogeneous across firms. This study provides implications for banking companies to enhance the quality and differentiation of ESG disclosure and serves as a reference for future research.